2014
DOI: 10.4238/2014.june.10.3
|View full text |Cite
|
Sign up to set email alerts
|

Biolistic transformation of wheat using the HMW-GS 1Dx5 gene without selectable markers

Abstract: ABSTRACT. Genetic manipulation using linear DNA was applied to the common wheat variety Xindong No. 26 via particle bombardment with the aim to improve bread-making quality of flour. Initially, 2 biolistic parameters, helium pressure and target distance, were optimized using plasmid pAHC25. We transformed wheat immature embryo scutella with the linear 1Dx5 gene without selectable markers. The highest transient β-glucuronidase expression was obtained when scuttles were bombarded at 1100 psi with a 9-cm target d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Cai et al (2013) studied the effects of different media on biolistic transformation efficiency, and obtained highest percentage (65%) of transgenic plantlets by the procedure: the calli were induced on Cu 2+ containing medium and pre-cultured for 4 d before biolistic-mediated transformation, followed by culturing on R medium. Qin et al (2014) obtained transgenic wheat overexpressing 1Dx5 gene without selectable markers from immature embryo scutella by optimizing the biolistic parameters. found that embryo with some endosperm residues after 4°C overnight in soaking could improve the frequency of callus induction and regeneration in wheat mature embryo culture system.…”
Section: Biolistic-mediated Transformationmentioning
confidence: 99%
“…Cai et al (2013) studied the effects of different media on biolistic transformation efficiency, and obtained highest percentage (65%) of transgenic plantlets by the procedure: the calli were induced on Cu 2+ containing medium and pre-cultured for 4 d before biolistic-mediated transformation, followed by culturing on R medium. Qin et al (2014) obtained transgenic wheat overexpressing 1Dx5 gene without selectable markers from immature embryo scutella by optimizing the biolistic parameters. found that embryo with some endosperm residues after 4°C overnight in soaking could improve the frequency of callus induction and regeneration in wheat mature embryo culture system.…”
Section: Biolistic-mediated Transformationmentioning
confidence: 99%
“…Згідно з опублікованими даними, більшість трансгенних рослин пшениці отримані за допомогою прямого переносу генів -біолістичним методом (Altpeter et al, 1996;Lazzeri, Jones 2009;Vasil et al, 1992;Weeks et al, 1993;Zhou et al, 1995;Qin et al, 2014;Hamada et al, 2017). Тим не менш, така трансформація має ряд обмежень та недоліків, основним з яких є можливі перебудови перенесених ДНК касет та мультикопійність, що зумовлюють «замовчування» відповідних генів (Бончук и др., 2014: пат.…”
unclassified